British Painting '74. - Campbell, Robin; Forge, Andrew; Lynton, Norbert (London : Arts Council of Great Britain, 1974)
Adams, Norman ; Agar, Eileen ; Aitchison, Craigie ; Allen, Richard ; Atkins, Raymond ; Ayres, Gillian ; Barrett, Tom ; Beattie, Basil ; Bellany, John ; Bennett, Mick ; Berg, Adrian ; Blake, Peter ; Blow, Sandra ; Buchanan, Anne ; Buckley, Stephen ; Burra, Edward ; Camp, Jeffery ; Carter, John ; Caulfield, Patrick ; Charlton, Evan ; Ciobotaru, Gillian Wise ; Clough, Prunella ; Cohen, Bernard ; Cook, Barrie ; Copnall, John ; Creme, Benjamin ; Davie, Alan ; Derham, Brigid ; Dilworth, Norman ; Donagh, Rita ; Dubsky, Mario ; Elderfield, John ; Evans, Merlyn ; Fielding, Brian ; Forster, Noel ; Frost, Terry ; George, Patrick ; Golding, John ; Gopal-Chowdhury, Paul ; Grant, Duncan ; Greaves, Derrick ; Green, Alan ; Green, Anthony ; Halliday, Trevor ; Hambling, Maggi ; Hamilton, Richard ; Haughton, David ; Heath, Adrian ; Hempton, Paul ; Hepher, David ; Heron, Patrick ; Hill, Anthony ; Hilton, Roger ; Hitchens, Ivon ; Hodgkin, Howard ; Hosking, Knighton ; Hoyland, John ; Hubbard, John ; Hughes, Patrick ; Huxley, Paul ; Irvin, Albert ; James, Richard ; Jaray, Tess ; Johnson, Elaine ; Jones, Allen ; Jones, Patrick ; Jones, Trevor ; Joseph, Peter ; Kalkhof, Peter ; Kidner, Michael ; Kiki, John ; Kinley, Peter ; Kitaj, R.B. ; Kossoff, Leon ; Lancaster, Mark ; Leverett, David ; Lowe, Peter ; Marshall, Rita ; Martin, Kenneth ; Masoero, Jeanne ; Mayer, Michael ; McLean, John ; Mead, Dorothy ; Medley, Robert ; Middleditch, Edward ; Miller, Alan ; Milow, Keith ; Moon, Jeremy ; Moon, Michael ; Mundy, Henry ; Murphy, Myles ; Newsome, Victor ; Pearson, David ; Phillips, Peter ; Phillips, Tom ; Plumb, John ; Quick, Bob ; Rees, Ronnie ; Riley, Bridget ; Rogers, Claude ; Rosenbloom, Paul ; Scott, William ; Scully, Sean ; Setch, Terry ; Smith, Jack ; Smith, Richard ; Spence, John ; etc.
biografie, bibliografie
British Painting '74, 26 September - 17 November 1974
Engels
boek
Keywords: Groot-Brittannië